Pengembangan Matriks Penilaian Program Sarjana Sembilan Standar Berbasis Excel dan Visual Basic for Application (VBA) - Nanda Noor Fadjrin; Ninik Agustin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
This research develops a Microsoft Excel application based on the Visual Basic for Application (VBA) Assessment Matrix of 9 Standard Bachelor Programs with product advantages. They are a matrix display with simpler sentences, accreditation assessment, a dashboard of assessment results, and an information system following LKPS to facilitate the manufacture of LEDs based on Quadrant Evaluation. The 4-D development design method is carried out through 4 stages: define, design, develop, and dissemination. The defined stage includes an analysis of the needs of study program managers facing accreditation, an assessment matrix of 9 standard study programs, and dashboard analysis. The design stage includes the selection of the calculation format, dashboard format, and the initial design of the Excel program (prototype I). The development stage is the validation of the initial product design, with the results of the assessment of the content aspect being 4,6250 valid criteria, displaying 4,3750 valid criteria and 4,1250 valid criteria for programmers (prototype II). Limited trials were carried out on all members of SPMI UNUGHA. Each item scored more than or equal to 3.75, with an average of 4.3276, which means it is feasible with a very good rating. (prototype III). The first year the field trial was conducted at the Nahdlatul Ulama University Mathematics Study Program, Purwokerto. Each item scored more than or equal to 3.75, with an average of 4.1354, which means it is feasible with a very good rating. (prototype IV). The dissemination stage (prototype 4) is carried out in two forms: scientific publications in SINTA accredited national journals (INSANIA: Journal of Alternative Educational Thought) and intellectual works: Microsoft Excel applications based on Visual Basic for Application (VBA) Undergraduate Program Assessment Matrix 9 Standards. (Final project).